Weeding Out or Developing Capacity? Challenges for Aboriginal Teacher Education - Kitchen, Julian; Cherubini, Lorenzo; Trudeau, Lyn; Hodson, Janie (Alberta Journal of Educational Research, 2010)
Teacher education is critical to the development of Aboriginal teachers able to ensure success among Aboriginal learners and contribute to the preservation and renewal of Aboriginal communities. In a series of talking circles, six beginning Aboriginal teachers discussed their teacher preparation and their first years of practice. They expressed concerns about teacher training programs that they regarded as assimilationist and a need for teacher education that helps Aboriginal teachers examine their individual and cultural identities in order to become effective teachers. Tribal Critical Race Theory (TribalCrit) is used as a discursive framework for critiquing existing approaches and offering culturally responsive alternatives.